Diagnostic Test as Formative Test in Mathematics Learning: A Meta-Analysis Study - Riyantika, Era; Firda, Jihan Zulfia; Sholikhah, Ummu (Jurnal Analisa, 2024)
Students have diverse learning abilities; thus, the role of the teacher as a facilitator is profoundly needed. Teachers have to recognize the initial abilities of each student through assessment activities so that teachers can identify students' abilities. This article aims to determine the influence of using diagnostic tests as a formative test in improving mathematics outcomes. The method used is meta-analysis by comparing information from several identical literature studies. Based on the analysis of 4 literature, diagnostic tests can improve students' learning outcomes by forming a heterogeneous group. A comparison of students' learning improvement can be observed by the percentage of learning mastery results before and after the diagnostic test, which carries out a statistical test, paired t-test. Students' learning outcomes were assessed by the percentage of learning mastery before and after using diagnostic tests, which were then processed using a statistical test paired sample. The test showed that the average increase in learning outcomes from the pretest was 63.93 to 81.68. It indicates that the student's learning outcomes have improved after using a diagnostic test as a formative test in mathematics learning.